2019
DOI: 10.1155/2019/1425281
|View full text |Cite
|
Sign up to set email alerts
|

TFIIIB Subunit Bdp1 Participates in RNA Polymerase III Transcription in the Protozoan Parasite Leishmania major

Abstract: Leishmania major, a protozoan parasite that diverged early from the main eukaryotic lineage, exhibits unusual mechanisms of gene expression. Little is known in this organism about the transcription factors involved in the synthesis of tRNA, 5S rRNA, and snRNAs, transcribed by RNA Polymerase III (Pol III). Here we identify and characterize the TFIIIB subunit Bdp1 in L. major (LmBdp1). Bdp1 plays key roles in Pol III transcription initiation in other organisms, as it participates in Pol III recruitment and promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
(78 reference statements)
1
6
0
Order By: Relevance
“…Immunofluorescence assays showed that LmBrf1 is a nuclear protein ( Figure 2 ). A similar punctate nuclear signal was reported for other Pol III transcription factors in L. major and T. brucei , including Bdp1 [ 33 ] and Maf1 [ 41 ], as well as for the L. major 5S rRNA genes [ 29 ]. Even though the vast majority of LmBrf1 signal is nucleoplasmic, a small part of the immunostaining colocalized with Nop56 in the nucleolar periphery, which could support the association of LmBrf1 with the rRNA transcription unit that was found in ChIP experiments ( Figure 5 ) and the possible interaction with proteins involved in Pol I transcription ( Table 1 ), as discussed below.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Immunofluorescence assays showed that LmBrf1 is a nuclear protein ( Figure 2 ). A similar punctate nuclear signal was reported for other Pol III transcription factors in L. major and T. brucei , including Bdp1 [ 33 ] and Maf1 [ 41 ], as well as for the L. major 5S rRNA genes [ 29 ]. Even though the vast majority of LmBrf1 signal is nucleoplasmic, a small part of the immunostaining colocalized with Nop56 in the nucleolar periphery, which could support the association of LmBrf1 with the rRNA transcription unit that was found in ChIP experiments ( Figure 5 ) and the possible interaction with proteins involved in Pol I transcription ( Table 1 ), as discussed below.…”
Section: Discussionsupporting
confidence: 71%
“…As shown in Figure 2 B, LmBrf1 is localized in the nucleus of the parasites, as anticipated for a transcription factor. The nuclear distribution of LmBrf1 is very similar to that of LmBdp1 [ 33 ]. Notably, a small fraction of LmBrf1 seems to colocalize with the nucleolar protein Nop56 in the periphery of the nucleolus (in yellow in the Merge panels of Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations